Shunt Active Power Filter System Design for Inter-harmonic - Zhang Chao; Ren Zi-Hui; Zhang Yi-Jun; Ma Xiao-Ping (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
Given the complex situations of the grid with inter-harmonics, three-level model of shunt active power filter (SAPF) was built. For the harmonics accurate detection, the CPT principle was used to detect the fundamental component of the grid. The inter-harmonics, parameter fluctuation of APF and the deadband effect were considered as the non-periodic disturbance to the controller. To eliminate the non-periodic disturbance impact on the controller and to improve the control system performance, equivalent input-disturbance (EID) was used based on the traditional repetitive controller. With Matlab and three-level test platform, the SAPF control system was built. The performance of detection and compensation for harmonic and inter-harmonic was verified by the simulation and experiment.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4442